2015
DOI: 10.1109/taffc.2015.2415212
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Dirichlet Process Mixture Model for Music Emotion Recognition

Abstract: This study proposes a novel multi-label music emotion recognition (MER) system. An emotion cannot be defined clearly in the real world because the classes of emotions are usually considered overlapping. Accordingly, this study proposes an MER system that is based on hierarchical Dirichlet process mixture model (HPDMM), whose components can be shared between models of each emotion. Moreover, the HDPMM is improved by adding a discriminant factor to the proposed system based on the concept of linear discriminant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Self collected [17], [18], [19], [20], [21], [22] RECOLA [23] CAL500 [24], [25], [26] Magna Tag A Tune [27], [28] MSD [27], [29] AMG 1608 [30], [31], [32] MER60 [30], [33] DEAP [34], [35], [36] Mediaeval [37], [38], [39] GTZAN [16] Marsyas [40]…”
Section: Dataset Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Self collected [17], [18], [19], [20], [21], [22] RECOLA [23] CAL500 [24], [25], [26] Magna Tag A Tune [27], [28] MSD [27], [29] AMG 1608 [30], [31], [32] MER60 [30], [33] DEAP [34], [35], [36] Mediaeval [37], [38], [39] GTZAN [16] Marsyas [40]…”
Section: Dataset Related Workmentioning
confidence: 99%
“…Low mean squared error [66] F-measure [18], [24], [25], [78], [107] Accuracy [19], [37], [38], [39], [48], [61], [67], [78], [99] , [101], [108] Specificity [61] AuC [27] Pearson Correlation Coefficient [68], [109] R 2 statistics [3], [15], [38], [40], [65], [79], Precision [24], [25], [26] , [78], [107] Recall [24], [26], [78], [107] RMSE [39] Equal error rate [77]…”
Section: Related Workmentioning
confidence: 99%
“…Extensive numerical results showed that the dimensionality-reduced features lead to better classification accuracy, comparing to the original features. Wang et al [7] explored a non-parametric Bayesian approach for emotional characterization of music. To construct a discriminative latent space while capturing correlations between emotions, they used a hierarchical Dirichlet process (HDP) mixture and modified it by introducing linear discriminant idea into the sampling distributions of HDP latent topics.…”
Section: Featured Workmentioning
confidence: 99%
“…The mission of the special section is to provide a view at the state-of-the-art in this domain and point to the potentially interesting future research directions. It therefore features articles concerning multimedia affective understanding from different perspectives, including predicting likability and emotions from users' responses [3], [4], content analysis for music affective understanding [5], [6], [7], visual content analysis for aesthetics and emotional understanding [8], [9], [10], and an application for sentiment analysis [11].…”
mentioning
confidence: 99%
“…R ecently, a large amount of music has become available to users, and efficient music information retrieval technology is therefore necessary to retrieve musical pieces desired by the users. Many methods related to genre classification [1], [2], [3], [4], [5], [6], [7], artist identification [8], [9], music mood classification [10], [11], [12], [13], instrument recognition [14], [15], [16], [17] and music annotation [18], [19] have been proposed to help users retrieve desired musical pieces. Although these methods can help users to retrieve desired musical pieces from music databases, retrieving desired musical pieces from enormous music databases is still a laborious task.…”
Section: Introductionmentioning
confidence: 99%